Evaluation of Drug Prescription Pattern Using WHO Prescribing Indicators in Libya: A Cross-Sectional Study - Ahmed Atia; Nouran Gzllal; Malak Gharibe (College of Pharmacy University of Baghdad, 2023)
Background and aims. The improper use of drugs due to irrational prescriptions is a common problem in Libya. This study aimed to investigate the prescribing pattern and predictors of antibiotic prescription in primary health care facilities in three districts (east, west, and south) in Libya. Methods. In this retrospective study, 484 prescriptions were examined. World Health Organization-recommended indicators for rational use were examined (WHO): e.g., the percentage of prescriptions covering antibiotics, prescription of injections, and prescription of drugs by a generic name and from a national essential drug list, as well as the average number of drugs per prescription, were all considered. Results. The average number of drugs per prescription was 4.72, with a maximum of 7 drugs in a prescription, and the percentage of prescriptions involving antibiotics and injections was 30.4% and 10.5%, respectively. There were 28.6% drugs prescribed by their generic name and 82.8% were retrieved from the essential drugs list. The most common category of medicines were 18.9% antibiotics, 18.3% antihypertensives, and 15.7% multivitamins and minerals. While the lowest consumed drugs were steroids 2.5%. Conclusion. There was some irrational drug prescribing, particularly with regard to injections and antibiotics. It is suggested that physicians participate in continuing education programs on rational prescribing for various medical indications.